How broadband internet affects labor market matching - Manudeep Bhuller; Andreas Ravndal Kostøl; Trond C. Vigtel (Norges Bank, 2020)
How the internet affects job matching is not well understood due to a lack of data on job vacancies and quasi-experimental variation in internet use. This paper helps fill this gap using plausibly exogenous roll-out of broadband infrastructure in Norway, and comprehensive data on recruiters, vacancies and job seekers. We document that broadband expansions increased online vacancy-postings and lowered the average duration of a vacancy and the share of establishments with unfilled vacancies. These changes led to higher job-finding rates and starting wages and more stable employment relationships after an unemployment-spell. Consequently, our calculations suggest that the steady-state unemployment rate fell by as much as one-fifth.
hdl:11250/2655637
Keywords: D83; J63; J64; L86; 330; Unemployment; Information; Job Search; Matching